Challenges to Mean-Based Analysis in Psychology: The Contrast Between Individual People and General Science - Marek McGann (Frontiers Research Topics, 2016)
In a recent paper we (Speelman & McGann, 2013) argued that psychology's reliance on data analysis methods that are based on group averages has resulted in a science of group phenomena that may be misleading about the nature of and reasons for individual behaviour. The paper highlighted a tension between a science in search of general laws on the one hand, and the individual, variable, and diverse nature of human behaviour on the other. This Research Topic explored this concern about the pitfalls of using the mean for the basis of psychological science. The problem is universal in its applicability to psychology, and opinion papers, reviews, and original empirical research from all areas of the discipline were invited. A total of 16 authors contributed 9 articles to the Topic. The range of issues that the authors viewed through the lens provided is impressive. The papers in this collection include a range of perspectives that provide concrete examples of how to approach research design, data collection, and analysis differently. No one contribution will provide a solution to our multifarious challenges, but nor should it. Our subject matter is complex and subtle, our investigations and methodological techniques will need to be equally so.